Peran Teknologi dalam Transformasi Pendidikan: Perspektif dari Studi Kepustakaan - Abdurrahman Abdurrahman; Dorce Idie; Anna Maria Hilda Songbes; Runi Arrang; Muhammad Wahyudi; Melda Agnes Manuhut (Journal on Education, 2024)
The transformation of education in the digital era leverages various technologies to enhance accessibility, effectiveness, and the overall quality of learning. Digital learning, virtual reality, and augmented reality provide innovative learning experiences, while data analytics and machine learning support personalized learning. Internet of Things (IoT) technology monitors health and resource efficiency in school environments. Blockchain reinforces the security of academic data and facilitates credential verification. Learning Management Systems (LMS) offer a centralized platform for the distribution of learning materials and online collaboration. Artificial Intelligence (AI) technology supports personal tutoring and cheating detection. Mobile learning (M-Learning) introduces learning through mobile devices, while robotics and School Information Management Systems (SIM School) aid in building interactivity and administrative efficiency. The utilization of these technologies not only transforms how we learn and teach but also creates an adaptive and responsive educational environment in the digital age.